2002
DOI: 10.1557/jmr.2002.0466
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerate-free BaTiO3 particles by salt-assisted spray pyrolysis

Abstract: Optimum conditions for the synthesis of nonagglomerated BaTiO 3 particles by salt-assisted spray pyrolysis (SASP) were investigated. The effect of particle residence time in the reactor and salt concentration on the crystallinity and surface morphology of BaTiO 3 was examined by x-ray diffraction and scanning electron microscopy. Mixtures of a metal chloride or nitrate salt, dissolved in aqueous precursor solutions, were sprayed by an ultrasonic atomizer into a five-zone hot-wall reactor. By increasing the sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…In general, these salts serve as a molten medium (called as molten salts) for solid reactants during high-temperature reactions, which enables a facile transport of reactants to attain their highly crystalline state within a relatively short time [ 22 ]. The molten salts also help in preventing the aggregation of reactant particles as they cover and stabilize the surface of the particles [ 22 , 25 ]. Several researchers have also added alkali salts in FSP to produce lanthanide–doped Y 2 O 3 phosphors [ 23 , 24 ]; however, they could not control the particle size to the submicron range, thus leaving scope for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these salts serve as a molten medium (called as molten salts) for solid reactants during high-temperature reactions, which enables a facile transport of reactants to attain their highly crystalline state within a relatively short time [ 22 ]. The molten salts also help in preventing the aggregation of reactant particles as they cover and stabilize the surface of the particles [ 22 , 25 ]. Several researchers have also added alkali salts in FSP to produce lanthanide–doped Y 2 O 3 phosphors [ 23 , 24 ]; however, they could not control the particle size to the submicron range, thus leaving scope for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, controlling their size, morphology and crystalline nature has been achieved by the incorporation or in situ generation of inert or reactive salts such as NaCl, NaNO 3 or KNO 3 during USP [13][14][15]. However, relatively little research has been carried out on nanoscale materials with both 1D structure and single-crystalline nature.…”
Section: Introductionmentioning
confidence: 99%
“…Spray pyrolysis, which is a gas-phase reaction process, was applied to the preparation of metal oxide nanopowders. [34][35][36][37][38] Okuyama et al reported salt-assisted spray pyrolysis for the preparation of aggregation-free metal oxide nanopowders. [34][35][36][37] The composite of a washable metal salt and a metal oxide prepared by spray pyrolysis transformed into metal oxide nanopowders after washing with water.…”
Section: Introductionmentioning
confidence: 99%